Comparative Study of Morphological Characteristics and Body Composition between Basketball Players from Second Leagues in Montenegro and Serbia - Velisa Vukasevic (Journal of Anthropology of Sport and Physical Education, 2018)
The purpose of this study was to describe morphological characteristics and body composition of the Second League basketball players from Montenegro and Serbia as well as to make comparation between them. Forty-eight males were enrolled in the study, divided into two groups: twenty-four senior players from the Second Basketball League of Montenegro and twenty-four senior players from the Second Basketball League of Serbia. Morphological characteristics were evaluated by a battery of four variables: body height, body weight, arm span and length of the leg. Body composition were evaluated by a battery of one variables: fat percentage of body. The standard central and dispersive parameters of all variables were calculated. The significance of the differences between the Second League basketball players from Montenegro and Serbia was determined by a t-test for small independent samples. The results showed that a significant differences was no found for any variable among the group. Therefore, these findings may give coaches knowledge that Montenegrin players have a good morphological potential, in that segment are not lagging behind for the Serbian players, whose players make excellent results at international competitions.